Dynamic Tribology Protocol (DTP): Response of salivary pellicle to dairy protein interactions validated against sensory perception. (April 2021) - Fan, Nengneng; Shewan, Heather M.; Smyth, Heather E.; Yakubov, Gleb E.; Stokes, Jason R.
Abstract: Saliva plays a key role in oral lubrication that is hypothesised to influence the oral processing and sensory perception of foods, beverages and oral care products. Here, we consider whether or not ex vivo saliva-lubricity measurements can provide insight into the oral texture perception of dairy beverages. A dynamic tribological protocol (DTP) is utilised to characterize the friction response of skim milk and whey protein isolate (WPI) mixtures upon interaction with an ex vivo salivary film (referred to as the saliva pellicle). This film is formed by adsorbing acid stimulated human saliva to hydrophobic elastic substrates. Trained sensory panellists perform a descriptive sensory analysis on the same sample systems. Samples evaluated include a set of dairy protein solutions at a matched solid content of 9% and a second set at matched protein content of 3.15%, whereby within each set the casein:whey protein ratio (C:W) is varied. It is found that the lubricity of the saliva pellicle decreases on contact with the dairy solutions, and the degree of decrease in lubricity increases with increasing C:W. We found friction parameters from DTP strongly correlate to the in-mouth textural attributes of thickness and smoothness, and after-feel attributes of mouth coating and smoothness. No such correlations were found across the whole set of samples when using friction measurements with no salivary film present or with their viscosity. The DTP with saliva-coated substrates offers a closer mimic to the oral processes and gives relevant insight into texture mouthfeel perception during and following consumption of dairy systems. Future work should investigate the usefulness of the DTP method more broadly for other beverage and food systems. Graphical abstract: Image 1 Highlights: In-mouth sensory texture perception is not simply a function of beverage composition. Dynamic tribological protocol (DTP) with an adsorbed saliva layer is relevant to sensory perception. Friction coefficient from DTP with saliva correlates with sensory smoothness, and mouth-coating. Friction coefficient on bare elastomer does not correlate with sensory texture of dairy beverages. At neutral condition, casein and whey both contribute to the interaction with saliva.